2009
DOI: 10.1185/03007990903421994
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with injectable antidiabetic agents in members with type 2 diabetes in a commercial managed care organization

Abstract: Persistence was low for injectable antidiabetics at 1 year among treatment-naïve patients. Patients who received insulin glargine, insulin detemir, or exenatide were more likely to persist than patients receiving NPH insulin. Older patients were more likely to persist, but sex, copayment and number of oral antidiabetic medications at initiation of the injectable antidiabetic were not associated with persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 19 publications
4
53
0
1
Order By: Relevance
“…et al 10 , Cooke et al 15 , and Bonafede et al 16 , but lower than some other estimates in the literature 11,12,17 percentile of the time between the first and second refills among those with at least two refills, stratified by quantity supplied. Findings from the sensitivity analyses in the current analysis also demonstrate the effects of using different criteria used to characterize persistence: allowing for gaps in basal insulin use of up to 60 days, 90 days, 120 days, or shorter than 90th percentile of the days between two consecutive fills would respectively characterize 40%, 55%, 65%, and 44% of the sample as being persistent within the year after treatment initiation.…”
Section: Factors þ Outcomes Associated With Basal Insulin Persistencementioning
confidence: 72%
See 2 more Smart Citations
“…et al 10 , Cooke et al 15 , and Bonafede et al 16 , but lower than some other estimates in the literature 11,12,17 percentile of the time between the first and second refills among those with at least two refills, stratified by quantity supplied. Findings from the sensitivity analyses in the current analysis also demonstrate the effects of using different criteria used to characterize persistence: allowing for gaps in basal insulin use of up to 60 days, 90 days, 120 days, or shorter than 90th percentile of the days between two consecutive fills would respectively characterize 40%, 55%, 65%, and 44% of the sample as being persistent within the year after treatment initiation.…”
Section: Factors þ Outcomes Associated With Basal Insulin Persistencementioning
confidence: 72%
“…With regards to basal insulin in particular, studies have found that approximately 55-80% of people with T2DM (identified from large commercial insurance databases) who were prescribed insulin glargine remained treatment persistent within the year after initiation [11][12][13][14] . In a separate study evaluating persistence with injectable antihyperglycemic medications among a managed care population, Cooke et al reported that 29% of patients initiating basal insulin or exenatide were persistent at 12 months after initiation 15 . In yet another study, Bonafede et al found that 27% of basal insulin initiators had uninterrupted use in the year after initiation 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been performed to evaluate persistence in patients prescribed OADs, but less in patients receiving insulin therapy, although renouncement to insulin leaves the patients with limited choice of anti-diabetes therapy [1317]. Most of these studies were conducted in the US.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] In reality, patients taking insulin glargine have been shown to be more likely to persist with their medication than those taking NPH insulin. 23 In general, treatment complexity for chronic conditionsincluding, though not limited to the need to administer more than one injection daily-correlates with poor adherence. 24 Although there are data in support of the clinical benefits of basal insulins, there is currently a paucity of realworld information about the impact of different basal insulin regimens on healthcare utilisation, employee disability and their associated costs from an employer's perspective.…”
Section: Introductionmentioning
confidence: 99%